Cognitive apprenticeship in vocational students mathematical decision making skills - Rina Oktaviyanthi; Indri Lestari (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2023)
Exploring the decision-making abilities of undergraduate students, including students from vocational education backgrounds, is the main priority in the achievement of mathematics learning in general and in Calculus courses particularly. Decision-making processes require cognitive guidance through activities describing in detail the systematic steps of each process. It is implicitly said as part of a cognitive apprenticeship procedure. There are claims that students with a vocational education background can develop their academic and practical potential more through a cognitive apprenticeship model. In addition, using video as visual media learning allows students to sharpen their skills. Therefore, the study aims to explore the distinction in achievement and improvement of mathematical decision-making skills between undergraduate students who learn with a Video-assisted Cognitive Apprenticeship approach (CAV), and they are who receive Cognitive Apprenticeship learning (CA) with conventional learning. A quantitative study with the Static-Group Pretest-Posttest Design was employed as a methodology in the research. Based on the research stage, there are differences in achievement and improvement of student decision-making skills with a review of the type of vocational school between undergraduate students.